purpose of cooperation, solidarity, Solidarity and Forgiveness it in stories of the prophets in the Holy Qur'an - Hussein, Ahmed Oleiwi; Abdulrahman, Alhassan Ali (Thi Qar Arts Journal, 2022)
Islam came with legislation that urges people to do good, and prevents them and discourages them from doing evil. It is known from the religion by necessity, that all the rulings legislated in our religion are in various aspects; It is only prescribed to bring benefit to them, and repel corruption from them in religion and this world. The stories of the prophets carry great meanings and goals, which are expressed through exhortations and sermons. We draw great lessons from it. It is an applied example that tightens the buttons and sharpens the determination, when the Muslim learns about the history of the previous nations. We discussed important legal purposes from the general and comprehensive purposes of Sharia, even if the sayings of scholars differed in counting them among them. Scholars have proven that the rulings in Islamic Sharia are legislated and linked to goals, objectives and meanings that are inseparable from achieving interests and warding off evils from people in both worlds .The research consists of two sections, and it shows various general legal purposes. We sought to extract it from the Quranic stories that tell the stories of the prophets. We worked on extracting these purposes from the jurists' deduction of the rulings mentioned in those stories. The value and importance of writing lies in the jurists’ protest and inference from some of the rulings mentioned in those stories; They deduced some of the legal rulings from them, taking into account the possibility of inferring the evidence of laws from us in terms of acceptance and rejection. And that one of the advantages of the stories of the prophets contained in the Qur’anic stories is the power of influence in the hearts of Muslims, as it represents a great ideological and educational incentive .